Changing Times? Public Perceptions and Knowledge About Parole - Small, Taylor (Université d'Ottawa / University of Ottawa, 2020)
In Canada, parole has become increasingly difficult to obtain over the last several decades. This resistance is arguably rooted – at least partially – in a number of high-profile parole violations and changes to both the laws and practices governing parole that are almost certainly a reflection of wider fear of crime and the rise of the risk society. This increased difficulty in obtaining parole should be seen as a concern (rather than the correct or most appropriate response) given that parole is believed to be a major step in the successful reintegration of offenders into the community (Parole Board of Canada, 2016). Within this context, it is intriguing to note the very recent increase in the use of parole in Canada. However, there has been very little academic research conducted to explain or understand this new phenomenon. Given that actual policies and practices governing parole are often influenced by public opinion/attitudes (Roberts, Stalans, Indermaur, & Hough, 2003), one possible explanation may reside in the current knowledge/perceptions of parole held by Canadians. Unfortunately, despite earlier research (Roberts, 2004), our understanding of public attitudes regarding parole is still very limited. In particular, little is known about recent public knowledge of this correctional release procedure and perceptions regarding its use. Through the use of a survey questionnaire, this study presents an updated view of public perceptions and knowledge about parole. Further, it examines potential correlations between these two constructs. The results reveal little public knowledge of parole and generally ‘negative’ perceptions of it. Further, little evidence was found to support the notion that these current attitudes differ in any significant way from findings reported in earlier polls. In conclusion, the recent increase in the use of parole does not seem to be rooted in changes in Canadians’ knowledge or perceptions of it.
Keywords: Parole; Public Opinion; Public Perception; Public Knowledge